2009
DOI: 10.1080/10888700902956151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adoption Agency Breed Identification and DNA Breed Identification of Dogs

Abstract: Governmental and other agencies may require dog caregivers (owners) to provide breed identification of their dogs. This study compares breed identification by adoption agencies with identification by DNA analysis in 20 dogs of unknown parentage. Of the 20 dogs who had been adopted from 17 different locations, the study identified 16 dogs as having (or probably having) 1 or 2 specific breed(s) in their ancestry. DNA analysis of these dogs indicated that 25% (4/16) did in fact contain genetic evidence of an adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 5 publications
1
41
1
Order By: Relevance
“…This conclusion echoes the general complexity and disagreement about dog breed identification found in previously published literature (Voith et al, 2009, 2013), but our study is the first truly cross-country comparison focused primarily on bull breeds. Ironically, there are marked differences between countries regarding what a pit bull is even though the United Kingdom's Dangerous Dog Act defines pit bull-type dogs according to the American Dog Breeders Association standard of conformation as published in Volume 1, Issue 3 of the Pit Bull Gazette in 1977 (DEFRA, 2009).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This conclusion echoes the general complexity and disagreement about dog breed identification found in previously published literature (Voith et al, 2009, 2013), but our study is the first truly cross-country comparison focused primarily on bull breeds. Ironically, there are marked differences between countries regarding what a pit bull is even though the United Kingdom's Dangerous Dog Act defines pit bull-type dogs according to the American Dog Breeders Association standard of conformation as published in Volume 1, Issue 3 of the Pit Bull Gazette in 1977 (DEFRA, 2009).…”
Section: Discussionsupporting
confidence: 88%
“…Determining whether a dog is a banned breed, however, is not always straightforward, as even experts struggle to determine visually whether a dog is a pit bull type (Rowan, 1986), and there can be extreme phenotypic and behavioral variation within a litter sired by the same stud and dam (Scott & Fuller, 1965). Furthermore, recent research has shown both a lack of agreement across individuals tasked with identifying cross-breeds and a lack of consensus between visual breed identification and genetic breed identification (Voith, Ingram, Mitsouras, & Irizarry, 2009; Voith et al, 2013). This confusion is likely to be even further compounded when dealing with the sensitive issue of bull breed identification.…”
mentioning
confidence: 99%
“…Unless the animal' s pedigree is known, the reported breed is likely based on visual identification, which may not necessarily correspond with results of breed identification through DNA testing. 25 For instance, pit bull-type dogs were among the most common dogs reported as purebred, although the designation pit bull has been challenged as being vague and for being applied to various mixes of pit bull types. 26 Estimation of age by use of the given birth date and last encounter date is another potential limitation, given the reliance on owners to accurately report the birth date.…”
Section: Discussionmentioning
confidence: 99%
“…And, as several recent studies comparing visual and DNA-based identification of dog breeds have shown, there is an extremely high rate of error in visual identification, especially when it comes to pit bull -type dogs. 8 Indeed, pit bulls' category problems mean that, instead of being made legible through their genealogy, documentation, or the testimony of their owners, these dogs are often read through a vague correlation between looks and breed. Malcolm Gladwell, among others, describes this type of "I know it when I see it" identification as a form of profiling.…”
Section: "Pit Bulls"mentioning
confidence: 99%